MONETARY POLICY AND ISLAMIC BANK STABILITY IN INDONESIA - Imronjana Syapriatama; Intan Kusuma Pratiwi (Journal of Enterprise and Development (JED), 2021)
The purpose of this paper is to examine the role of monetary policy to Islamic Bank Stability in Indonesia from January 2007 to December 2020. The policy is presented by Bank Indonesia 7DRR while Islamic Bank Stability uses Islamic Bank Z-score. This paper also employs several variables as control variable in order to manage effectiveness of the model. This paper uses Autoregressive Distributed Lag method (ARDL) in order to investigate the long run and short run effect between selected variables. The results reveal that the policy does not affect the Islamic Bank Stability in the long run. It only affects the Stability in the short run. The result also implies that tightening policy is responded by Islamic Bank Stability based on the financial environment.